Screening of high-risk deleterious missense variations in the CYP1B1 gene implicated in the pathogenesis of primary congenital glaucoma: A comprehensive in silico approach - Muhammad, Shahid; Ahmad, Azfaralariff; Muhammad, Tufail; Nazeer Hussain, Khan; Ahmed Abdulkareem, Najm; Sabika, Firasat; Muhammad, Zubair; Shazrul, Fazry; Law, Douglas (PeerJ Publishing, 2022)
Background Primary congenital glaucoma (PCG) is the most common subtype of glaucoma caused by defects in the cytochrome P450 1B1 (CYP1B1) gene. It is developing among infants in more than 80% of cases who exhibit impairments in the anterior chamber angle and the trabecular meshwork. Thus, a comprehensive in silico approach was performed to evaluate the effect of high-risk deleterious missense variations in the CYP1B1 gene.